Find the smallest real root of the polynomial 4 5 x 4 + 4 x − 2 7 8 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You are great!!
Log in to reply
We usually ought to mention an equation rather than just an expression or function for roots instead of factors.
Log in to reply
No. Both are acceptable.
Log in to reply
@Pi Han Goh – I checked from a website. You are right. Good to be treated like this though.
https://en.wikipedia.org/wiki/Complex conjugate root_theorem
The website above indicates that there is no need to stand for equation only but root of a polynomial is well acceptable. Sorry for my mistake.
Nice Solution I used Graphing calculator to find the minimum but this gave a different variety to solve a problem and how do you think of such awesome methods to solve a question!
Log in to reply
Like Cardano's method. This is a standard way to determine the exact roots of a quartic equation. Unfortunately, there' no standard formulas for polynomials of degrees above 4.
± 2 . 8 0 3 8 0 1 7 8 9 i should be ± 2 . 8 0 3 8 0 1 9 8 9 i .
With a graphing calculator TI-83 PLUS and window, Xmin=-3, Xmax=- 2.75::::: Ymin=-20, Ymax=20.
2nd TRACE (CALC),2 (ZERO) enter. Adjest the cursor so Y is as near 0 as possible.
For Y=.2039, we get x=
−
2
.
8
0
6
6
7
7
Just a graph plotter can solve this. But the art of solving is important which I did not show.:)
Problem Loading...
Note Loading...
Set Loading...
Divide both sides by 4 5 :
x 4 + 4 5 4 x − 5 3 0 9 = 0
Now, try to factor that into the form ( x 2 + p x + q ) ( x 2 − p x + r ) = 0 . Expand and compare the coefficients:
q + r = p 2 r − q = 4 5 p 4 q r = − 5 3 0 9 . . . ( 1 ) . . . ( 2 ) . . . ( 3 )
From ( 1 ) and ( 2 ) solve for p and q :
q = 2 p 2 − 4 5 p 4 , r = 2 p 2 + 4 5 p 4
Substitute in ( 3 ) , expand, clear denominators and simplify:
p 6 + 5 1 2 3 6 p 2 − 2 0 2 5 1 6 = 0
Now, compare that equation with the identity ( u + v ) 3 − 3 u v ( u + v ) − ( u 3 + v 3 ) = 0 . Another system will be formed:
p 2 = u + v 3 u v = − 5 1 2 3 6 u 3 + v 3 = 2 0 2 5 1 6 . . . ( 4 ) . . . ( 5 ) . . . ( 6 )
Divide ( 5 ) by 3 and cube both sides:
u 3 v 3 = − 1 2 5 6 9 9 3 4 5 2 8
Now, make an equation in z with roots u and v :
( z − u 3 ) ( z − v 3 ) = 0 ⟹ z 2 − ( u 3 + v 3 ) z + u 3 v 3 = 0
z 2 − 2 0 2 5 1 6 z − 1 2 5 6 9 9 3 4 5 2 8 = 0
Solve it using the quadratic formula:
z = 2 0 2 5 8 ± 1 6 8 9 6 1 7 2 7 3 0 9
So:
u = 3 2 0 2 5 8 + 1 6 8 9 6 1 7 2 7 3 0 9
v = 3 2 0 2 5 8 − 1 6 8 9 6 1 7 2 7 3 0 9
p 2 = u + v = 3 2 0 2 5 8 + 1 6 8 9 6 1 7 2 7 3 0 9 + 3 2 0 2 5 8 − 1 6 8 9 6 1 7 2 7 3 0 9
From here, let's work only with approximations:
p = 3 2 0 2 5 8 + 1 6 8 9 6 1 7 2 7 3 0 9 + 3 2 0 2 5 8 − 1 6 8 9 6 1 7 2 7 3 0 9
p ≈ 0 . 0 0 5 6 5 3 5 7 6 1 2 7
Obtain q and r :
q ≈ − 7 . 8 6 1 2 8 1 6 2 , r ≈ 7 . 8 6 1 3 1 3 5 8 3
So, our original equation factors as:
( x 2 + 0 . 0 0 5 6 5 3 5 7 6 1 2 7 x − 7 . 8 6 1 2 8 1 6 2 ) ( x 2 − 0 . 0 0 5 6 5 3 5 7 6 1 2 7 + 7 . 8 6 1 3 1 3 5 8 3 ) = 0
By solving each factor with the quadratic formula we get:
x 1 ≈ 2 . 8 0 0 9 7 2 3 5 1
x 2 ≈ − 2 . 8 0 6 6 2 5 9 2 7
x 3 , 4 ≈ 0 . 0 0 2 8 2 6 7 8 8 0 6 3 ± 2 . 8 0 3 8 0 1 7 8 9 i
The smallest one is x 2 = − 2 . 8 0 6 6 2 5 9 2 7 .